Drivers of farmers' intentions to use eco-breeding: Integrating the theory of planned behavior and the norm activation model - Wang, Xingdong; Lu, Pan; Tang, Jin; Gao, Xueping; Liao, Wenmei; Weng, Zhenlin (Frontiers in Environmental Economics, 2022)
Ecological breeding (eco-breeding) is a systematic ecological farming method for the benefit of the environment and human health, but farmers have adopted this method only to a lesser extent. The main objective of this study was to examine the factors that influence farmers' intentions to use eco-breeding methods. The study model was a combined application of the theory of planned behavior (TPB) and the normative activation model (NAM) to investigate the intentions of 527 Chinese farmers to engage in eco-breeding practices. Structural equation modeling analysis revealed that although the farmers' intention to adopt eco-breeding practices was influenced by both self-interested and altruistic motives, self-interested motives had a greater impact on the farmers' choices. Furthermore, favorable attitudes had the greatest effect on the farmers' intentions to implement eco-breeding, while past habits had no statistically significant effect on the intentions. Nonetheless, past habits significantly influenced attitudes and perceived behavior control in the combined model. In addition, the findings indicated that awareness of consequences had a significant effect on personal norms and the attribution of responsibility. Overall, the findings demonstrate the good efficiency as well as comprehensiveness of the integrated TPB-NAM in explaining the farmers' intentions to engage in eco-breeding practices. This study increases our understanding of the factors influencing the farmers' adoption of eco-breeding practices and helps to promote the adoption of eco-breeding in rural areas while providing a basis for the development of eco-breeding policy interventions.